2016
DOI: 10.1364/aop.8.000156
|View full text |Cite
|
Sign up to set email alerts
|

Diffraction gratings: from principles to applications in high-intensity lasers

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
87
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(95 citation statements)
references
References 166 publications
0
87
0
3
Order By: Relevance
“…7(a)): the lower the incubation fluence, the higher the damage density. This difference is likely due to the electric field enhancement with the corrugation, 19 considering that damage precursors are the same for both samples.…”
Section: B Interpretation Of Damage Results Obtained On Different Sumentioning
confidence: 99%
“…7(a)): the lower the incubation fluence, the higher the damage density. This difference is likely due to the electric field enhancement with the corrugation, 19 considering that damage precursors are the same for both samples.…”
Section: B Interpretation Of Damage Results Obtained On Different Sumentioning
confidence: 99%
“…Bragg-type gratings can be applied as couplers for laser diodes, in optical fibers (to reflect light in the fibers or for mode coupling in multimode fibers), for data storage and many others. [14] The structures that cause light diffraction occur in several places in nature. This type is often referred to as a thin grating.…”
Section: Diffraction Gratingsmentioning
confidence: 99%
“…As we shall see here, both changes are desired in LC gratings. [14] The structures that cause light diffraction occur in several places in nature. [15][16][17][18][19][20][21] Indeed, grating-like structures (periodic structures) are very common in nature, such as the periodicity of gene segments in biological body which leads to the diversity of biology; distribution periodicity of energy band determines the transportation of electrons and thereby influences the conductivity and dielectricity of the materials.…”
Section: Diffraction Gratingsmentioning
confidence: 99%
“…• It is demonstrated that, in contrast to conventional spatially periodic static gratings [6,16,[60][61][62][63][64], in a STP grating each spatial diffraction order is composed of an infinite number of temporal harmonics, each one of which is diffracted at a certain angle of diffraction.…”
Section: Introductionmentioning
confidence: 99%